Determination of Optimal Number of Relays Using a New Energy Model for WSN - Bhattacharya, Partha Pratim; Gupta, Shilpi; Pal, Nupur (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
Wireless Sensor Networks are proving themselves as a boon to the surroundings and its deployment is a prominent area to be considered for minimum energy consumption. In this paper, we have considered deployment of a sensor grid network for 36 and 100 number of sensor nodes. Diagonally opposite nodes are considered to be source and destination. Using a modified energy model, the energy consumption for direct path and that with different number of relays are calculated. The maximum distance up to which direct transmission is possible and the number of required relays for higher transmission distances are then found out.